2017
DOI: 10.1589/jpts.29.941
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prolonged racing on muscle activity and spatiotemporal variables: double-poling technique

Abstract: [Purpose] The purpose of this study was to examine the effect of a 40-minute race on muscle activity and spatiotemporal cycle variables at four-time points during a 12-km roller skiing test using the double-poling technique. [Subjects and Methods] Five elite cross-country (XC) skiers on the Korean National reserve team participated in the study. Part of a biathlon course that consisted of both flat land and slopes was selected, and three measurements were recorded after every 4-km lap. Spatiotemporal variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The present study showed a race speed decrease over the laps, paralleled by both CL and CR reductions ( Table 2 ). Kim et al ( 2017 ) showed a decrease over a simulated 12-km roller skiing race using the double poling technique. When considering double poling similar to G3 (because both techniques require parallel upper-limb pushes supporting ski gliding), Kim et al ( 2017 ) findings are akin to the present study regarding race speed decrease and its determinants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study showed a race speed decrease over the laps, paralleled by both CL and CR reductions ( Table 2 ). Kim et al ( 2017 ) showed a decrease over a simulated 12-km roller skiing race using the double poling technique. When considering double poling similar to G3 (because both techniques require parallel upper-limb pushes supporting ski gliding), Kim et al ( 2017 ) findings are akin to the present study regarding race speed decrease and its determinants.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al ( 2017 ) showed a decrease over a simulated 12-km roller skiing race using the double poling technique. When considering double poling similar to G3 (because both techniques require parallel upper-limb pushes supporting ski gliding), Kim et al ( 2017 ) findings are akin to the present study regarding race speed decrease and its determinants. Ohtonen et al ( 2018 ) showed how a simulated 20-km race in skating style worsened final sprint performance using G3.…”
Section: Discussionmentioning
confidence: 99%